FTIR Spectroscopic and Chemometric Investigations of Ancient Potteries, belonging to 4th-6th Century BC, excavated in Ancient Ainos (Enez)-Turkey - Başaran, Sait; AKYÜZ, SEVİM (My University, 2018)
Ancient potteries are important source of materials on many aspects of the past such as civilization, trade and technology. Potteries are made of clayminerals and the common major clays used in making potteries are in smectite or kaolinite group of clay minerals. Clay minerals as the main material for the production of potteries show some characteristic reactions during the firing; e.g. dehydroxylation, decomposition and phase transformation. Thus, the firing conditions can be estimated by the absence or occurrence of the specific mineral assembly. IR spectroscopy, in conjuction with x-ray diffraction, is a powerful tool for clay mineral analysis, thus for the mineralogical characterization of potteries. Using the infrared spectra, unique information about the group of minerals in which the specimen belongs, the degree of crystalline and non-crystalline impurities can be determines and reactions of minerals with chemicals in their environment can also inferred. Recently the IR spectroscopic data is used together with statistical analysis methods such as Principal Component Analysis (PCA) and Cluster Analysis for grouping / provenance studies of potteries. in this study a set of twenty pottery fragments, coming from archaeological excavation in EnezTurkey, was investigated by FT-IR and Chemometric techniques, XRD was used as complimentary technique. FT-IR data provided a detailed description of the minerals contained in the pottery findings, whereas the chemometric analyses were found to helpful to find the similarities between the samples, which gaye meaningful interpretation to archeological studies. The whole set of samples shows a general similarity in the mineralogical composition, compatible with the geological conformation of Enez. Enez area is famous by clay deposits. The illite and montmorillonite were the main clays of this area. Calcite concentration was found to different in all samples but presence of also microcline indicated that CO3is primary and comes as impurity of the local clays. Feldspar phases were inferred from the second derivative profiles of the IR spectra. The absence of any firing mineral in the ceramic body is a clear indication of low firing temperature. Dark brown and black coloration was due to different concentrations of Mn02, magnetite and red coloration was due to hematite. Spectroscopic results indicated that the potteries were fired to a temperature less than 8000C in the oxid izi ng atmosphere.
Keywords: FTIR spectroscopy; Ancient ceramics; Chemometric analysis